Periodontal reconstruction by heparan sulfate mimetic-based matrix therapy in Porphyromonas gingivalis-infected mice. Issue 8 (August 2018) - Coyac, Benjamin R.; Detzen, Laurent; Doucet, Philippe; Baroukh, Brigitte; Llorens, Annie; Bonnaure-Mallet, Martine; Gosset, Marjolaine; Barritault, Denis; Colombier, Marie-Laure; Saffar, Jean-Louis
Abstract: Background: Periodontitis is a set of chronic inflammatory diseases affecting the supporting structures of the teeth, during which a persistent release of lytic enzymes and inflammatory mediators causes a self-perpetuating vicious cycle of tissue destruction and repair. A matrix-based therapy using a heparan sulfate (HS) analogue called ReGeneraTing Agent (RGTA) replaces destroyed HS by binding to available heparin-binding sites of structural molecules, leading to restoration of tissue homeostasis in several inflammatory tissue injuries, including a hamster periodontitis model. Methods: The ability of RGTA to restore the periodontium was tested in a model of Porphyromonas gingivalis -infected Balb/cByJ mice. After 12 weeks of disease induction, mice were treated weekly with saline or RGTA (1.5 mg/kg) for 8 weeks. Data were analyzed by histomorphometry. Results: RGTA treatment restored macroscopic bone loss. This was related to (1) a significant reduction in gingival inflammation assessed by a decrease in infiltrated connective tissue, particularly in cells expressing interleukin 1ß, an inflammatory mediator selected as a marker of inflammation; (2) a normalization of bone resorption parameters, i.e. number, activation and activity of osteoclasts, and number of preosteoclasts; (3) a powerful bone formation reaction. The Sharpey's fibers of the periodontal ligament recovered their alkaline phosphatase coating. This was obtained while P. gingivalis infection was maintained throughout the treatment period. Conclusions: RGTA treatment was able to control the chronic inflammation characteristic of periodontitis and blocked destruction of periodontal structures. It ensured tissue regeneration with recovery of the periodontium's anatomy.